Pengaruh Penggunaan Metode Pembelajaran Brainstorming Terhadap Kemampuan Menulis Teks Berita Siswa Kelas VIII SMP Negeri 1 Sagranten - Andriyanto, Methatya Suci; Supendi, Deden Ahmad; Agustiani, Tanti (Jurnal Ilmiah Wahana Pendidikan, 2023)
The brainstorming learning method can be used as a learning method to help improve students' ability to write news texts. The purpose of this study was to see the effect of using the brainstorming learning method on the ability to write news texts in class VIII B students at SMP Negeri 1 Sagaranten. The research method used is a quantitative method with research type experiments. Furthermore, this study used a one group pretest and posttest design. The use of the brainstorming learning method to improve the ability to write news texts can be seen by giving pretest and posttest to students. The pretest given to students of class VIII B, namely before being given treatment and the posttest, is a test given to students VIII B after being given treatment using the brainstorming method. So that after carrying out the pretest and posttest, the average pretest score was 58.79 while the posttest average score was 79.50. Then the N-gain test was carried out to see the difference between the pretest and posttest values, the result of the N-gain value was 0.4771 with moderate criteria. Furthermore, the results of the Hypothesis Test for the t-test of the paired sample test hypothesis are accepted because it shows that H0 is rejected in other words, Ha is accepted because the tcount is 8.51 > ttable 2.069, which means that the brainstorming learning method affects the ability to write news texts for class VIII B students of SMP Negeri 1 Sagaranten Academic Year 2022/2023. Keywords: brainstorming methods and writing ability